Voluntary risk reporting in annual reports: Case study of the practices of Polish public companies - Monika Wieczorek-Kosmala; Joanna Błach; Maria Gorczyńska (e-Finanse: Financial Internet Quarterly, 2014)
Grounded on literature review on risk disclosures and risk reporting practices, the paper aims to explore the extent and content of voluntary risk reporting practices of non-financial companies. Annual reports, focusing on several areas of concern of sampled public companies from three different sectors were subject to content analysis combined with morphology analysis. The results show that the extent of risk disclosure within non-financial risk exposure is broad and not connected with the sector, which is similar to findings within the cohesion of reported risk exposure with those provided in the so-called "top 10 risk" rankings. However, disclosures concerning risk management practices visibly differ among the analysed sectors. The paper contributes to the existing debate on the need and practice of risk reporting by providing insight into practices of non-financial companies operating in Poland as an emerging economy.
Keywords: M48; G34; G38; 330; risk reporting; risk disclosures; risk management; annual reports